2022
DOI: 10.3390/s22239278
|View full text |Cite
|
Sign up to set email alerts
|

Digital Biomarkers of Gait and Balance in Diabetic Foot, Measurable by Wearable Inertial Measurement Units: A Mini Review

Abstract: People with diabetic foot frequently exhibit gait and balance dysfunction. Recent advances in wearable inertial measurement units (IMUs) enable to assess some of the gait and balance dysfunction associated with diabetic foot (i.e., digital biomarkers of gait and balance). However, there is no review to inform digital biomarkers of gait and balance dysfunction related to diabetic foot, measurable by wearable IMUs (e.g., what gait and balance parameters can wearable IMUs collect? Are the measurements repeatable?… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…There is considerable recent work that has reported ways in which IMUs might be used for the assessment of standing postural stability and in the assessment of gait outcomes across a wide range of research disciplines [16][17][18][19][20][21][22][23]. In our sister study we demonstrated how IMUs might be used to assess the UTT-30 [11].…”
Section: Discussionmentioning
confidence: 67%
“…There is considerable recent work that has reported ways in which IMUs might be used for the assessment of standing postural stability and in the assessment of gait outcomes across a wide range of research disciplines [16][17][18][19][20][21][22][23]. In our sister study we demonstrated how IMUs might be used to assess the UTT-30 [11].…”
Section: Discussionmentioning
confidence: 67%
“…Inertial-based sensors, such as IMUs, consisting of accelerometers and gyroscopes, and sometimes with the addition of magnetometers, are widely used in different applications [ 100 , 101 , 102 , 103 , 104 ]. Mainly used to obtain data on velocity, orientation and gravity force, their applications range from robotics to navigation and have been applied to medicine [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, wearable IMUs are used to monitor the safety behaviors of scaffolding workers [188], enhance human location with Wi-Fi sensing [189,190], count exercise repetition [191], and assessment of knee moments [192]. More applications of IMUs can be found in these reviews [193][194][195][196][197][198][199].…”
Section: Imumentioning
confidence: 99%